Chad : 2006 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Chad. (IMF Staff Country Reports; Country Report ;, 2007)
This 2006 Article IV Consultation highlights that despite some progress in macroeconomic stabilization and reform under IMF-supported programs during the 1990s, Chad's indicators on business climate, governance, and socioeconomic conditions still remain among the lowest in the world. In 2006, real GDP is expected to grow by 1.3 percent, reflecting higher non-oil growth offsetting a somewhat larger fall in oil production than envisaged earlier. Executive Directors have noted Chad's efforts in maintaining macroeconomic stability and in channeling resources to priority sectors despite a difficult political and security environment.